CAPS markers in plant biology - Y. N. Shavrukov (Вавиловский журнал генетики и селекции)
Cleaved Amplified Polymorphic Sequences (CAPS) markers are applicable in a wide range of tasksin plant biology. They have been developed for plant genetics and breeding and become especially useful. This mini-review analyzes information about the application of CAPS markers within the past3–5 years. In the presented study, special attention is focused on CAPS markers linked with genes controlling important agricultural traits in different crops. The main principles of the developmentand analysis of CAPS markers, as well as advantages and disadvantages of this type of molecular markers, are briefly outlined in the beginning of this review. CAPS markers are based on PCR amplification of DNA fragments with specific primers followed by digestion with restriction enzymes and separation of the products in agarose gel. Functional CAPS markers can be developed on the known sequence of a gene of interest for the analyses of its structure, function, expression, and regulation. CAPS closely linked to the gene of interest are especially helpful for Marker-Assisted Selection, and they are widely used in the breeding of wheat, barley, soybean, potato, tomato, and other crops for tolerance to various pathogens. CAPS markers are often used for the preparation of genetic maps and fine mapping of studied genes. For some plants, first moleculargenetic maps were prepared using CAPS. This method was also successfully used for the mapping of both individual genes and QTLs controlling such important traits as plant growth habit, grain quality, and tolerance to pathogens in cereals, as well as the shape of tomato fruit. CAPS have important applications in the analyses of genetic polymorphism and phylogeny, particularly, in closely related species. Thus, CAPS are an effective tool for molecular-genetic research and plant breeding.